The effect of seismic loading on slope stability using limit equilibrium method - Mohd. Riza Aizad Shauri, 1988-; Aminaton Marto, supervisor; Fakulti Kejuruteraan Awam (2012)
Project Paper (Sarjana Muda (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2012